Formation of Proplastids in the Apical Meristem of Wheat - Galina A. Semenova (Journal of Plant Cell Development, 2018)
The apical meristem of the growing point of plants contains proplastids, precursors of chloroplasts. The main attention of investigators was paid to the transformation of proplastids into chloroplasts. The formation of proplastids of the apical meristem of wheat seedlings was investigated in the present work and described for the first time in the scientific literature. Ultrastructural images of apical meristem areas showed that the formation of the proplastide body includes several stages: localization of plastid DNA in the cytoplasmic matrix in close contact with cytoplasmic ribosomes, the formation of membrane vesicles containing plastid DNA, the step-by-step filling of these vesicles with dense contents, and the formation of mature proplastids.
Keywords: Triticum aestivum L.